-37=-3(5+m)

Simple and best practice solution for -37=-3(5+m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -37=-3(5+m) equation:


Simplifying
-37 = -3(5 + m)
-37 = (5 * -3 + m * -3)
-37 = (-15 + -3m)

Solving
-37 = -15 + -3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '3m' to each side of the equation.
-37 + 3m = -15 + -3m + 3m

Combine like terms: -3m + 3m = 0
-37 + 3m = -15 + 0
-37 + 3m = -15

Add '37' to each side of the equation.
-37 + 37 + 3m = -15 + 37

Combine like terms: -37 + 37 = 0
0 + 3m = -15 + 37
3m = -15 + 37

Combine like terms: -15 + 37 = 22
3m = 22

Divide each side by '3'.
m = 7.333333333

Simplifying
m = 7.333333333

See similar equations:

| (2x-3)-100=0 | | 0.11y+0.05(y+2000)=1540 | | 0.11x+0.05(y+2000)=1540 | | y=4(-2)-10 | | 4x-28=62+2x | | y^2-2y+56=0 | | 2/5.29= | | F(x)=20-0.4x | | 7x-9=4x-21 | | 5x+3x-2x=7-4+3 | | .11/9=x | | 4(2-x)+5=1 | | 6(x+9)=3x+39 | | (X^2+2x)-(x+2)=0 | | 5x-3x-2x=7-4+3 | | F(x)=-x^2-12x-36 | | 10x-6=8x+12 | | 9x+41=-4(x-7) | | 7x+13=9x-3 | | (-18x-12)-(-13x+17)= | | 2+2x=8x-102 | | (q+9)*5=35 | | 2-2x=8x-102 | | 5/6x-4=3 | | 5-9n=7 | | 3(-5+2y)-6y=-15 | | 0=(x-9)/5x | | 35a^4b^3+25a^2b=0 | | (5p+3r)+(10p-6r)= | | 35=5x+7(x-7) | | pi*x=6 | | 28/6=x |

Equations solver categories